SUPERCRITICAL FLUID CO2 EXTRACTION ON LICHEN Usnea barbata L. - Kiril Lisichkov; Stefan Kuvendziev (Journal of Engineering & Processing Management, 2011)
Non-conventional separation procedure - supercritical fluid CO2 extraction (SFE-CO2) conforms to the strict demands of the precise process eco-technologies. It represents a perspective method especially in obtaining eco-friendly extracts from vegetable and animal raw materials. The influence of operating parameters (raw material granulation, extraction fluid flow rate, operating pressure, operating temperature and extraction time) on the yield of extract and usnic acid, has been studied throughout the extraction process on Usnea barbata L., by application of supercritical CO2 (SFE-CO2). The separation process in all experiments was conducted at operating temperature of 25 ℃ and operating pressure of 50-55 bar. The extraction of active components from the lichens by supercritical CO2 was performed in a highpressure, extraction "pilot-plant" for processing solid raw materials.
Keywords: SFE-CO2; usnic acid; lichen